Hubungan Pola Asuh Orangtua dengan Kematangan Karir Siswa di MAN 2 Bukittinggi - Hidayat, Robi; Rahmi, Alfi (Indonesian Research Journal on Education, 2022)
This research was motivated by the observations of researchers who found that there were students who had unfriendly parenting, such as parents who were too neglectful or tended to reject emotionally or ignore the physical needs of their children. One of them is that there are students who are doubtful in choosing theircareers. The purpose of this study was to determine the relationship between parenting patterns and career maturity in students at MAN 2 Bukittinggi. The type of research used in this study is a quantitative approach, the research design used in this study is the correlational method. Based on the research results obtainedr_hitung = 0.564, then the hypothesis is accepted which states that there is a significant relationship between parenting and student career maturity, it means H_0 is rejected. This is because r_count = 0.564 which is in the coefficient interval 0.40-0.599 so that the level of correlation between the two variables is included in the medium category. . With a positive r value, which means that if that parenting has increased or decreased, it will also be followed by an increase or decrease in career maturity. From the correlation value obtainedpreviously that parenting style contributed 31.8% to career maturity. This figure shows that 31.8% career maturity is determined by parents and the rest is determined by other factors.